Al-Lugah al- ʻArabiyyah wa Ahammiyyat Tadrīsihā li Gayr al-Nāṭiqīn bi hā - Shalahuddin al-Nadwi (Al-Zahra : Journal for Islamic and Arabic Studies, 2005)
A good teaching of Arabic language must be based on linguistic rules, the using of appropriate methods and a new attractive curriculum in accordance with the development of education. Studies show that teaching of Arabic using classical methods require a long time and may result in saturation. In this article, the writer tries to suggest some new methods that are expected to make the teaching of Arabic language more lively and generally demanded by many people.